The harada-mori technique: Revisited - Agnes Immanuela Toemon; Handinata Indrawan; Sem Samuel Surja (Faculty of Medicine, Universitas Islam Indonesia, 2022)
More sensitive diagnostic methods for detecting worms’ eggs are needed in areas with low soil-transmitted helminth (STH) prevalence. The Harada-Mori technique was first introduced by Mr. Harada and Mr. Mori. This technique is easy, simple, and does not require sophisticated equipment. The Harada-Mori technique is based on larvae tropism nature in the water to concentrate the larvae of hookworms and Strongyloides stercoralis. Since its first application in 1955, this technique has undergone several modifications. The Harada-Mori could complement the Kato-Katz technique for faeces examination in areas with low STH infection intensity.